Icterícia neonatal: fatores associados à necessidade de fototerapia em alojamento conjunto - Vitória Silva Souza Dias; Simone Manso de Carvalho Pelicia; José Eduardo Corrente; Ligia Maria Suppo de Souza Rugolo (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: To investigate the frequency of neonatal jaundice and use of phototherapy, along with the risk factors associated with phototherapy in a rooming-in care (RC) setting. METHODS: This retrospective study included newborns with gestational ages ≥ 35 weeks seen in an RC setting at a tertiary hospital between October and December 2017. The subjects were divided into two groups, each featuring newborns treated or not treated with phototherapy. All newborns with a gestational age ≥ 35 weeks without congenital anomalies seen in an RC setting were included. Subjects requiring admission to the neonatal ward were excluded. Clinical data relative to the mothers, pregnancies, newborns, and care practices were analyzed. Endpoint: use of phototherapy. Associations between groups were assessed via Student's t-test and the chi-squared test. Multiple logistic regression was employed to identify independent factors associated with the use of phototherapy. RESULTS: Almost half (47%) of the 376 newborns included in the study developed jaundice, of which 66 (18%) were provided phototherapy. The treated group had a lower gestational age (38 vs. 39 weeks), higher umbilical cord bilirubin levels (2 vs. 1.5 mg/dL), greater weight loss (7 vs. 6%), greater incidence of ABO incompatibility (35 vs. 10%), and longer hospital stays (79 vs. 50 hours). Logistic regression found the following independent risk factors for phototherapy: gestational age (OR=6), umbilical cord bilirubin (OR=16), ABO incompatibility (OR=12), and weight loss (OR=1.24). CONCLUSION: Jaundice was a frequent finding in newborns on RC. Almost 20% of the newborns with jaundice unwere provided phototherapy. Weight loss was the only preventable risk factor for needing phototherapy. No protective factor was found.